Formulation of a bacterial - silt mixture for degrading hydrocarbons in crude oil-contaminated sediments - Hii Yii Siang (Universiti Putra Malaysia Terengganu, 2014)
Bacterial-silt mixture has been formulated to degrade hydrocarbons in crude oil contaminated sediments (1500 mg/kg Petronas Tapis A crude oil). The bacterial-silt mixture was formulated by inoculating an active oil degrading bacteria isolated from Malaysia marine environment into enriched marine silt.